2018
DOI: 10.1007/s11769-018-0990-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Pattern and Effect of Administrative Division Adjustment During Urbanization of China: Empirical Analysis on Multiple Scales

Abstract: The adjustment of administrative divisions is one of the important factors guiding China's urbanization, which has profound economic and social effects for regional development. In this paper, we comprehensively describe the process of the adjustment of administrative divisions at provincial and municipal levels in China and summarize the effects on the basic structure and patterns of the spatial development. We quantitatively assess the effects on fields such as urbanization and social economy through the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Table 10 shows the spatial effect on the house prices of Fuyang four years after the merger of Fuyang. Column (1) shows that the coefficient of interaction term T × D is 0.0624, which is significantly positive at the statistical level of 0.05, indicating that the housing prices within the range of 3-6 km away from the West Lake District increased by about 6.24% as compared to the benchmark group. Column (2) shows that the interaction term of T × D had a significantly negative impact on housing prices in Fuyang, with a coefficient of −0.11.…”
Section: The Spatial Effect Of the City-county Merger Of Fuyang On Homentioning
confidence: 95%
See 3 more Smart Citations
“…Table 10 shows the spatial effect on the house prices of Fuyang four years after the merger of Fuyang. Column (1) shows that the coefficient of interaction term T × D is 0.0624, which is significantly positive at the statistical level of 0.05, indicating that the housing prices within the range of 3-6 km away from the West Lake District increased by about 6.24% as compared to the benchmark group. Column (2) shows that the interaction term of T × D had a significantly negative impact on housing prices in Fuyang, with a coefficient of −0.11.…”
Section: The Spatial Effect Of the City-county Merger Of Fuyang On Homentioning
confidence: 95%
“…Faced with the above queries regarding the fact that the impact of city-county mergers on urban economic growth may be insignificant, other scholars sustained that the city-county merger is conducive for efficiency, fairness, and economic development. Yu [1], Martin and Schiff [9], Boyne [18], Hudnout [19], Faulk, and Hicks [20] have pointed out from an economic perspective that the amalgamation of city and county can reduce administrative duplication, which is conducive for the reduction of government financial expenditure and the realization of the economies of scale. Henderson [42] further argued that the merger directly brought about the growth of per capita income.…”
Section: The Impact Of City-county Merger On Urban Economic Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…The historical establishment of administrative divisions is based on national unity and political stability, and modern administrative division adjustments are implemented mainly to address the evolving needs of rapid economic and social development and urbanization (Zhou, 2008;Zheng and Kahn,2013;Wang and Liu, 2015). Yu et al (2018) provided a comprehensive summary of administrative division adjustments at the province and prefecture levels in China. They concluded that administrative division adjustments have been a major factor influencing the progress of urbanization progress and a substantial driving force for the evolution of the urban spatial structure in China.…”
Section: 1mentioning
confidence: 99%